MULHERES IDOSAS E O SANEAMENTO BÁSICO: reflexões sobre a precariedade da política pública em Breves-PA - LIMA, Elizandra Gomes (2023)
This Course Completion Work deals with basic sanitation as a state public policy, considering aspects related to gender, social inequalities, provision of services in the urban area and the precariousness of that public policy in the municipality of Breves-PA. The objective of this research is to reflect on the impacts caused by the inefficiency of the basic sanitation policy on the daily life of elderly women participating in the CCFV and residing in the Aeroporto neighborhood in Breves-PA, considering the changes caused after the Covid-19 pandemic. The research is of a qualitative nature, the methodology used was bibliographical, documental and field research. Among the theoretical references used are: Perrot (2007), Faleiros (2004), Ribeiro and Rooke (2010) and others. Along with the theoretical references, it was necessary to use laws, decrees, federal, state and municipal plans, as well as images, articles from internet newspapers and other documents such as those released by Instituto Trata Brasil (2018) and (2022). In this sense, it was found that the basic sanitation policy includes water supply services, sanitary sewage, collection and treatment of solid waste and management of rainwater, however, in the municipality of Breves-PA, with regard to the neighborhood airport, locus of the research, is not effective in its amplitude. Because, despite the legal apparatus that regulate its existence and implementation nationwide, the municipality does not offer even half of the necessary services, causing the precariousness of public policy and the inefficiency of the services provided to the Marajoara elderly population residing in the researched neighborhood. This time, elderly women are being harmed in various aspects of their lives, from their physical and psychological health to income, time, in addition to the consequences of the lack of sanitation affecting their descendants.